2020
DOI: 10.4103/ijmm.ijmm_20_260
|View full text |Cite
|
Sign up to set email alerts
|

Optimal size of Sample Pooling for RNA Pool Testing: An Avant-Garde for Scaling up Severe Acute Respiratory Syndrome Coronavirus-2 Testing

Abstract: Background and Objectives: Timely diagnosis is essential for the containment of the disease and breaks in the chain of transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The present situation demands the countries to scale up their testing and design innovative strategies to conserve diagnostic kits and reagents. The pooling of samples saves time, workforce and most importantly diagnostic kits and reagents. In the present study, we tried to define the pool size that could … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Several countries have been using pool testing as a successful strategy for the population wide screen of SARS-CoV-2 infection (Khodare et al , 2020). Recently, attempts been made to understand the sensitivities of the SARS-CoV-2 detection real time kits in pool testing set up and feasibility.…”
Section: Resultsmentioning
confidence: 99%
“…Several countries have been using pool testing as a successful strategy for the population wide screen of SARS-CoV-2 infection (Khodare et al , 2020). Recently, attempts been made to understand the sensitivities of the SARS-CoV-2 detection real time kits in pool testing set up and feasibility.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of efficiency gain is performed differently in the analyzed research studies. Many of them discuss thoroughly the sensitivity of pools, but report efficiency data only about a single clinical application [ 9 , 10 , 19 , 20 , 21 , 22 ,]. Other papers evaluate, at least approximately, the probability of obtaining a negative pool or the expected number of tests required, as a function of N , vf , and pool size, s [ 11 , 12 , 15 , 16 , 22 ].…”
Section: Pooling Scheme: the Theoretical Point Of Viewmentioning
confidence: 99%
“…The dilution effect due to pooling was considered to be of varying importance among the studies, which is likely because, in the different experimental settings, samples with different viral loads were pooled. Arvind and colleagues [ 20 ] investigated the pool size in depth on the basis of different viral loads. Clinical samples previously tested as positive but with a different range of Ct values of the E gene target were chosen, serially diluted with negative sample elutes, and tested by RT-PCR to determine whether they remained detectable.…”
Section: Type Of Pooling: Technical Laboratory Aspectsmentioning
confidence: 99%
“…Late April, a report from Saarland University, Germany, indicated that positive sample with a relatively mild viral load from asymptomatic patients could still be detected within pools of 30 [21]. Further works suggest that RT-qPCR viral detection can been achieved in pools with a number of samples ranging from 5 to 64 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%